Prisms of prejudice : mediating the Middle East from the United States - Wilkins, Karin Gwinn, 1962- (University of California Press, 2021)
"Media do not reflect: media refract. In the United States, established and enduring prisms of prejudice about the projected "Middle East" are mediated through popular culture, broadcast news, government mission statements and official maps. This mediation serves to assert political boundaries and construct the US as heroic against a villainous or victimized Middle East. These problematic maps and narratives are persistent over time and prevalent across genre, with clear consequences evidenced by the rise in discriminatory sentiments in the US population and experiences of harm in US Arab and Muslim communities. Exploring a wide range of media, Karin Gwinn Wilkins illuminates the shape and scope of these narratives and explores ways to counter these prisms of prejudice through informed and engaged strategic intervention"--